Introduction to Microsoft Sway as a Social Science Learning Media - Ilah Armilah -; Sugeng Widodo; M Mona Adha (International Journal of Educational and Life Sciences, 2023)
Education in social studies (IPS) has developed significantly in recent years. Technological breakthroughs have provided new opportunities to enhance the learning experience in these subjects. One interesting tool is Microsoft Sway, a digital presentation platform that offers flexibility and creativity in designing learning materials. This article is about the introduction of Microsoft Sway as a learning medium in Social Sciences (IPS) subjects. In this article the author will discuss the advantages, challenges, potential use and utilization of Microsoft Sway as a social studies learning medium. This approach will combine a literature review and practical guidance to illustrate the potential of Microsoft Sway in a social studies learning context.